Conceptual Bases of the İmpact of Ethnic Conflicts on Regional and İnternational Security - Najafov Zafar Nuri (Britain International for Academic Research (BIAR-Publisher), 2021)
The article examines the impact of ethnic conflicts on regional and international security. It is noted that during the Cold War, it was impossible to conduct serious research in this area. Because ethnic conflicts were seen as an internal affair of states. However, with the end of the Cold War, the collapse of absolute sovereignty intensified the interaction between the domestic life of the country and the international community. Such a development in the context of globalization has turned ethnic conflicts into a problem of international politics, taking them out of the context of the internal affairs of states. The globalization of ethnic conflicts has strengthened its impact on regional and international security and laid the groundwork for the